Recommendations and Strategies to Mitigate Environmental Implications of Artificial Island Developments in the Gulf - Muhammad Salman Afzal (19418875) (2022)
Artificial island development (AID) to tackle rampant urbanization on scarce land puts all marine biodiversity at huge risk and is recognized as a global conservation issue worldwide. This study critically reviews the gaps that undermined biodiversity and ecology during construction activities of the artificial islands in the Gulf region that could be alleviated if apposite environmental values and sustainable strategies of different regions of the world had paid enough heed to economic and social aspects. The method used for this study was an analytical descriptive literature survey, and the resources were chosen after three phases of quality assessment. This survey found various barricades to sustainable AID, such as lack of scientific data, adequate site selection, ineffective environmental evaluations, noncompliance with legislation, and economic gains over the environmental aspects. It was concluded that to protect the marine ecosystem from inevitable degradation, strict compliance with international and national legislation, research and baseline data collection, strengthening of the existing environmental assessment, continuous capacity building, and modern practices of different countries should be brought to the forefront. Furthermore, this study aims to provide guidance to policymakers and governmental organizations to mitigate emerging environmental issues during AID through strategic decision-making processes. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su14095027